Pendidikan Multikultural Berbasis Kearifan Lokal (Studi Kasus pada Tradisi Makan Berhadap Suku Melayu) - Nurabiyah, Nurabiyah; Ibrahim, M. Maulana; Hanum Ok, Azizah (STAI Ihyaul Ulum Gresik, 2022)
Multicultural education is one of the important aspects in building diversity and tolerance in society. This research aims to explore the concept of multicultural education based on local wisdom, with a focus on the tradition of Makan Berhadap in the Malay Tribe as a case study. Makan berhadap is a tradition that teaches the values of togetherness, mutual cooperation, and respect for differences. This research uses a qualitative approach with a case study method, which observes and analyzes how this tradition acts as a learning medium in introducing multicultural values to the community. The results show that the tradition of eating together is not only a place for social interaction, but also serves as an informal educational tool that teaches mutual respect, cooperation, and appreciation of diversity. Therefore, local wisdom-based multicultural education such as makan berhadap has great potential to be implemented in the formal education curriculum, in order to create a generation that is more tolerant and sensitive to cultural diversity.